UMP QS 5 Star University to pursue good values, governance and integrity - Ishak, Ismail; Hasnah, Haron; Irene, Wei Kiong Ting (2018)
University Malaysia Pahang (UMP) one of the local technical universities has many success stories to tell. First, it can proudly claim itself to be the finest of all the technical universities, as it is the only one that was bestowed the 5 Star Rating by QS. Technically it claimed itself to be of equivalent of standard to research universities as it was the only one to receive the same as that of the research universities. This honor reflects the quality of teaching, research, publication and community services that it has undertaken that be leader of its pack. Not forgetting UMP has also undertaken many continuous improvement and innovation to its curriculum to meet future challenges which reflects UMP as a state of the art technical university.